Comparative Remission Rates and Tolerability of Drugs for Generalised Anxiety Disorder: A Systematic Review and Network Meta-analysis of Double-Blind Randomized Controlled Trials - Kong, Wenqiang; Deng, Huiyuan; Wan, Jie; Zhou, Yilu; Zhou, Yan; Song, Bihui; Wang, Xiuling (Frontiers in Pharmacology, 2020)
the goal of our study is to update evidence and determine the best advantageous drugs for GAD in remission rate and tolerability profiles.We performed a systematic review and network meta-analysis of double-blind randomized controlled trials. We searched seven electronic databases from their inception to March, 2020 to identify eligible double-blind, randomized controlled trials (RCTs) reporting the outcome of remission in adult patients who received any pharmacological treatment for GAD. Our outcomes were remission rate (proportion of participants with a final score of 7 or less on HAM-A) and tolerability (treatments discontinuations due to adverse events). We calculated summary odds ratios (ORs) and 95% confidence intervals (CIs) of each outcome via pairwise and network meta-analysis with random effects.Results: Twenty-eight trials were rated as moderate risk of bias, 4 trials as low. For remission rate, agomelatine (OR 2.70, 95% CI 1.74 - 4.19), duloxetine (OR 1.88, 95% CI 1.47 - 2.40), escitalopram (OR 2.03, 95% CI 1.48 - 2.78), paroxetine (OR 1.74, 95% CI 1.25 - 2.42), quetiapine (OR 1.88, 95% CI 1.39 - 2.55), and venlafaxine (OR 2.28, 95% CI 1.69 - 3.07) were superior to placebo. For tolerability, sertraline, agomelatine, vortioxetine, and pregabalin were found to be comparable to placebo. However, the others were worse than placebo in terms of tolerability, with ORs ranging between 1.86 (95% CI 1.25 - 2.75) for tiagabine and 5.98 (95% CI 2.41 - 14.87) for lorazepam. In head-to-head comparisons, agomelatine, duloxetine, escitalopram, quetiapine, and venlafaxine were more efficacious than tiagabine in terms of remission rate, ORs from 1.66 (95% CI 1.04 - 2.65) for duloxetine to 2.38 (95% CI 1.32 - 4.31) for agomelatine. We also found that agomelatine (OR 2.08, 95% CI 1.15 - 3.75) and venlafaxine (OR 1.76, 95% CI 1.08 - 2.86) were superior to vortioxetine. Lorazepam and quetiapine were poorly tolerated when compared with others drugs.Conclusions: Of these interventions, only agomelatine manifested better remission with relatively good tolerability but these results were limited by small sample sizes. Duloxetine, escitalopram, venlafaxine, paroxetine, and quetiapine showed better remission but poorly tolerated.